Kamingaw : an impressionist portrait of the Bisaya painter Martino A. Abellana - Fernandez, Raymund Lozada, 1955-; University of San Carlos Press (Talamban, Cebu City, Philippines : University of San Carlos Press, 2017)
This book presents, like an Impressionist painting, a portrait of the man, Martino Alcoseba Abellana: what he was like, what he believed in, what he did, and who he was. This bold task is best done with broad strokes; hopefully, to produce in the end what can only be a fleeting impression. This is not a book of history. An historic biography would be quite useful. But histories sometimes miss things that are easier apprehended by way of a more literary approach. This is the spirit that guides this writing. And yet it is written from the unique perspective of a student viewing his teacher and his teacher's art. This perspective is not without its inherent faults. This work ought to be read as a testimonial narrative. The extent of its objectivity and bias is discernable from the text itself. And as the reader may appreciate, the text's value lies in its personal quality. May this therefore serve as an invitation for others, including specialists of history and art studies, to present their own perspectives on this truly remarkable painter, teacher, and important man, who lived inside the continuing history of his Bisaya and Filipino culture.
CAS
Includes bibliographical references (page 181) and index.
Text in English.
Keywords: Abellana, Martino Alcoseba, -- 1914-1988.; Painters -- Philippines -- Visayan Islands -- Biography; Impressionist artists -- Philippines -- Visayan Islands -- Biography